Lupus nephropathy beyond immunosuppression: Searching for nephro and cardioprotection - Morales, Enrique; Sandino, Justo; Galindo, María (Frontiers in Nephrology, 2023)
Renal involvement in systemic lupus erythematosus (SLE) represents one of the most frequent organ manifestations, often leading to end-stage kidney disease (ESKD). Several therapies have been tested in patients with lupus nephritis (LN) to prevent further organ damage. The effectiveness of immunosuppressive therapy as a treatment for LN is abundant, supported by multiple clinical trials that have shown its efficacy in preventing the development of chronic kidney disease (CKD). In addition to immunosuppressive therapy, several traditional and recent therapies aimed at nephroprotection in patients with proteinuric chronic kidney disease are gaining importance in the setting of LN. Thus, immunosuppressive therapy should be accompanied by nephro- and cardioprotective measures to control cardiovascular risk factors and proteinuria to ensure a better renal prognosis. Despite this, the literature on these specific measures is relatively scarce, with recommendations focused on the blockade of the renin-angiotensin-aldosterone system (RAAS). This review explores the pharmacological options available for cardiovascular and renal protection outside the usual treatment schemes.